2010
DOI: 10.2478/s11756-010-0043-5
|View full text |Cite
|
Sign up to set email alerts
|

Macrozoobenthos response to environmental degradation in a heavily modified stream: Case study the Upper Elbe River, Czech Republic

Abstract: Benthic macroinvertebrates are an important indicator of river health. However, their response upon water quality development downstream the pollution outlets considerably depends on the environmental habitat characteristics. Three successive stretches, each of them providing three different mesohabitats in stillwater (S), torrential (T) and riparian (R) zones were selected for evaluation of the impact of altered metapotamal river bed morphology (channelization) and chemical determinants of water quality on th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 16 publications
0
9
0
Order By: Relevance
“…Many studies have sought to identify the patterns of macroinvertebrate distribution in both large geographical areas (Heino et al 2002) and small ones (Adámek et al 2010), showing a strong relationship between aquatic biota and environmental variables (Bonada et al 2005). To understand these influences on the composition of Oligochaeta assemblages in the Iguaçu River, we performed a canonical correspondence analysis (CCA).…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have sought to identify the patterns of macroinvertebrate distribution in both large geographical areas (Heino et al 2002) and small ones (Adámek et al 2010), showing a strong relationship between aquatic biota and environmental variables (Bonada et al 2005). To understand these influences on the composition of Oligochaeta assemblages in the Iguaçu River, we performed a canonical correspondence analysis (CCA).…”
Section: Discussionmentioning
confidence: 99%
“…Bleak, roach and chub formed the majority of the fi sh community in the Elbe River (Jurajda et al, 2010b), where Adámek et al (2010) reported a saprobity index in the range 1.97-2.46. In the Dyje River the index of saprobity was more favourable, as both localities exhibited better betamesosaprobity (1.70-1.80; Sukop et al, 2010), thus enabling barbel to be eudominant in Tasovice.…”
Section: : Relations Between Environmental Variables and Fish Speciementioning
confidence: 99%
“…Therefore, macroinvertebrate studies have been used for water quality assessments by several environmental monitoring programmes (Rosenberg and Resh, 1993;Dar and Ganai, 2017). While biological diversity in rivers is usually influenced by a combination of pressures from various anthropogenic impacts (Adámek et al, 2010), communities in headwater streams are affected namely by water velocity and associated physical forces (Allan and Castillo, 2007). Thus, in mountain streams an adequate dynamic approach reflecting rapidly changing currents and discharge needs to be considered in analysing their water environment.…”
Section: Introductionmentioning
confidence: 99%